A COMPARATIVE STUDY OF ULTRASOUND AND COMPUTED TOMOGRAPHY IN EVALUATION OF ACUTE AND CHRONIC PANCREATITIS, ASSOCIATED COMPLICATIONS AND PREDICTING SEVERITY AND PROGNOSIS - HARIHARAN, MAHESH; CHAIL, VIVEK; MUDDA, AMEET; MODI, PRIYA; RANGARI, MAYANK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: (1) The objective of the study was to determine the value of USG and computed tomography (CT) in early diagnosis of acute pancreatitis (AP). (2) The study aimed to compare which of the above two radiological investigations (USG/CT) provides the most important information of the disease process and to determine value of CT in evaluating complications, morbidity/severity, and predicting prognosis of AP using modified CT severity index (MCTSI). Methods: This study included 50 patients diagnosed with pancreatitis, consisting of 38 cases of AP and 12 cases of chronic pancreatitis (CP). Both USG and contrast-enhanced CT (CECT) were used to visualize the pancreas, assess its size, detect peripancreatic inflammation and fluid collections, and identify the extent of necrosis and complications. The sensitivity and specificity of USG and CECT were compared. The severity of AP was classified using the MCTSI within 3 days of symptom onset. Clinical outcomes, including hospital stay duration, organ failure, systemic infection, and the need for surgical intervention, were recorded and correlated with MCTSI scores. Statistical Package for the Social Sciences 22.0 was used for statistical analysis and p<0.05 was taken as statistically significant. Results: The mean age of patients was 37.92±12.14 years. USG had a sensitivity of 58% for detecting AP, significantly lower than the 95% sensitivity of CECT, primarily due to bowel gas interference. Both USG and CECT had high positive predictive values. The MCTSI effectively classified the severity of AP, with 41.5% of cases categorized as mild, 39% as moderate, and 19.5% as severe. Extrapancreatic complications were significantly correlated with adverse clinical outcomes and end-organ failure when included in the MCTSI scoring. USG was adequate for diagnosing CP through visualization of dilated ducts, calcifications, and atrophic pancreas, but CECT demonstrated higher specificity and accuracy, especially for rare forms like groove and mass-forming pancreatitis. The study showed a strong correlation between MCTSI scores and patient outcomes. The mortality rate was 2%, observed only in patients with severe AP. Conclusion: The MCTSI is a valuable tool for accurately classifying the severity of AP and predicting clinical outcomes. CECT is superior to USG in diagnosing and managing pancreatitis, providing better visualization and assessment of complications. While USG is useful for diagnosing CP, CECT offers greater specificity and accuracy. The study supports the use of MCTSI in routine clinical practice to guide the management and predict outcomes in patients with AP.